E-learning initiatives in e-ducating student teachers - Pang, Vincent; Lee, Kean Wah; Tan, Choon Keong; Shukery Mohamed (Penerbit UKM, 2005)
This paper reports a study of online learning at the School of Education and Social Development, Universiti Malaysia Sabah. It focused on the context of implementation and student perception on online learning in the school. The study involved 324 undergraduate students across all levels of study in the school. A questionnaire was used to collect data about their perception on the readiness of the school, the extent to which online learning was carried out, the opportunities and limitations of the learning mode, and student perception on online learning as a whole. Quest (Adams & Khoo, 1996), an interactive computer item analysis software, was used for data analysis. It was found that online learning helped to supplement the quality of teaching and learning. The students found that online learning was not only helpful, but also enjoyable and exciting. Online learning was perceived to be a better learning experience compared to face-to-face learning. It also helped students to take more initiative in their learning and development compared to the conventional classes. However, the school needs to improve the infrastructure and facilities of ICT for more effective use of online learning for the future.